2018
DOI: 10.1016/j.micres.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and assessment of two biocontrol bacteria against Pseudomonas syringae wilt in Solanum lycopersicum and its genetic responses

Abstract: Pseudomonas and Bacillus species are attractive due to their potential bio-control application against plant bacterial pathogens. Pseudomonas aeruginosa strain D4 and Bacillus stratosphericus strain FW3 were isolated from mine tailings in South Korea. In these potent bacterial strains, we observed improved antagonistic activity against Pseudomonas syringae DC3000. These strains produced biocatalysts for plant growth promotion, and in vivo examination of Solanum lycopersicum included analysis of disease severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…The latter described that Pseudomonas strains were able to produce appreciable amounts of cellulase in culture-free supernatants and inhibited the mycelial growth of both pathogenic fungi Pythium aphanidermatum and Rhizoctonia solani. In addition, our results are in complete agreement with the findings of Durairaj et al [50] who reported no cellulase activity in the potent bacterial strains B. stratosphericus FW3 and Pseudomonas aeruginosa D4.…”
Section: Discussionsupporting
confidence: 93%
“…The latter described that Pseudomonas strains were able to produce appreciable amounts of cellulase in culture-free supernatants and inhibited the mycelial growth of both pathogenic fungi Pythium aphanidermatum and Rhizoctonia solani. In addition, our results are in complete agreement with the findings of Durairaj et al [50] who reported no cellulase activity in the potent bacterial strains B. stratosphericus FW3 and Pseudomonas aeruginosa D4.…”
Section: Discussionsupporting
confidence: 93%
“…Considering that the leishmaniasis treatment with pentavalent antimonials is known to be ineffective and unsafe and therapies based on pentamidine and amphotericin B are considered toxic and exhibit recurrence rates, it is clear that new treatment alternatives are necessary [132][133][134][135][136]. Although widely described as a producer of antibacterial and antifungal compounds [41,42,[137][138][139], we emphasize that the Burkholderia species' antileishmanial activity was unknown so far. As we demonstrated in this study, Burkholderiales may offer promising candidates to treat neglected diseases of which resistance and toxicity of current treatments represent a global public health concern.…”
Section: Discussionmentioning
confidence: 99%
“…carotovorum cells. Bacillus species have been used as a biocontrol agent against different pathogenic fungi (Mates et al 2019) and bacteria (Azaiez et al 2018;Durairaj et al 2018).…”
Section: Discussionmentioning
confidence: 99%